2016
DOI: 10.1002/app5.122
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia's ‘Great Power’ Aspirations: A Critical View

Abstract: Indonesia is readying itself for a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…National interests of Indonesia and Saudi Arabia in protecting national economy and security as well as less consistency of domestic politics (in Indonesian context) will reduce their leadership capacity like how Fealy and White doubted Indonesia's regional role after the New Order [7]. Frictions among national leaders will influence international diplomacy and regional leadership in constructing prosperous and peaceful region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National interests of Indonesia and Saudi Arabia in protecting national economy and security as well as less consistency of domestic politics (in Indonesian context) will reduce their leadership capacity like how Fealy and White doubted Indonesia's regional role after the New Order [7]. Frictions among national leaders will influence international diplomacy and regional leadership in constructing prosperous and peaceful region.…”
Section: Discussionmentioning
confidence: 99%
“…They said "there remain very significant hurdles to be overcome before Indonesia could effectively function as a great power in the Asian strategic system. Its armed forces remain overwhelmingly focused on internal security and seem, under Jokowi, less focused on building up external capabilities" [1]. The World Bank reported that GDP of Indonesian growth increased from 4.9 in 2015 to 5.1 in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is neither strengthening its power projection capability nor building a coalition to address China's growing aggressiveness in the South China Sea (or at least to fulfill its security goal). In fact, as noted by Fealy and White (), Indonesian military modernization is not focused on maritime or power projection capabilities, which are needed to confront or check China's growing threat in the South China Sea. Instead, it is focused on strengthening the army to improve internal security functions.…”
Section: Introductionmentioning
confidence: 99%
“…Given its size, strategic location and economic potential as well as its success in navigating democratization culminating in the country's designation as an emerging democratic power, there has been increased interest among scholars in understanding the nature of Indonesian foreign policy. The extent to which Indonesia can seek a leadership role at the global level remains inconclusive where some see Indonesia indeed has played a greater role (Acharya 2014;Laksmana 2011) while others are not convinced (Fealy and White 2016;McRae 2014). Furthermore, in light of the democratization process, most recent studies on Indonesian foreign policy focus on how the democratization process shapes Indonesian foreign policy outcomes (Dosch 2008;Ruland 2010).…”
Section: Introductionmentioning
confidence: 99%